P576 Endoscopic healing with vedolizumab in Crohn's disease occurs predominantly in the first 6 months and is independent of serum concentrations: Data from LOVE-CD. (30th January 2023) - D'Haens, G; Bossuyt, P; Baert, F; Molnár, T; Clasquin, E; Lowenberg, M; Montazeri, N; Peeters, H; Lambrecht, G; Vermeire, S
Abstract: Background: Endoscopic healing is an important treatment goal in Crohn's disease (CD). Vedolizumab (VDZ) was shown to induce endoscopic healing after 6 months in a significantly greater proportion of pts with early CD than in those with late CD (>2 years)(UEGW 2022). We investigated whether further endoscopic healing could be attained with 6 more months of VDZ treatment in those pts with no SES-CD worsening at month 6 compared to baseline. Methods: Pts in the LOVE-CD study received standard doses of VDZ and had ileocolonoscopies at baseline, w26 and 52. We studied the kinetics of endoscopic improvement during continued VDZ treatment. Endoscopies were scored by independent readers. So far, 157 pts completed the LOVE-CD trial with available central reading results. We here report the results of 76 pts (48%) who had stable endoscopic diseases or any degree of endoscopic improvement at w26 with 3 centrally read endoscopy scores (baseline, w26 and 52) available at present. VDZ serum conc were also measured and correlated to endoscopic improvement. Results: We studied 76 pts (mean age 36.7, 51 (67%) female, median baseline SES-CD 10 (range 3-30) who reached w52 and had no SES-CD worsening at w26. We identified 3 endoscopic improvement patterns: 1) 24 pts (32%, 12 early, 12 late CD) with median baseline SES-CD 7.5 (range 3-21) had a SES-CD score of 0 at w26. Three of these pts had again mild lesions at w52 (SES-CD 1-4), the rest maintained SES-CD=0 at w52 (endoscopic healing); 2) 20 pts (26%, 6 early, 14 late CD) with median baseline SES-CD 8 (range 3-27) had a SES-CD of 1-3 at w26 (endoscopic remission defined as SES-CD<4). At w52, 10/20 had a score of 0, 7/20 the same score as at w26 and only 3/20 a higher score; 3) 32 pts (42%, 5 early, 27 late CD) with median baseline SES-CD 14 (range 5-30) had no endoscopic remission at w26 (SES-CD >4) with a drop to median SES-CD 7 (range 5-20) at w26 and further to median SES-CD 5 (range 0-15) at w52. Figure 1 shows the evolution of the SES-CD. The mean VDZ serum conc was (1) 19.36 mg/l at w26 and 22.23 mg/l at w52 in the group with endoscopic healing, (2) 19.52 mg/l at w26 and 21.69 mg/l at w52 in the group with endoscopic remission, and (3) 17.38 mg/l at w26 and 20.09 mg/l at w52 in the group without endoscopic healing or remission. Conclusion: In this subset of LOVE-CD pts with endoscopic improvement or unchanged SES-CD at w26, the majority of pts (44/76) reached endoscopic remission (SES-CD<4). Overall, endoscopic improvement in this subgroup of responders by SES-CD score was a median of 7 (range -1 to 25) SES-CD points between w0 and w26 and a median of 0 (range -10 to +15) SES-CD points between w26 and w52. The degree of endoscopic improvement beyond month 6 was unrelated to VDZ serum conc.